PTU-136 Heterogeneity in High Resolution Manometry (HRM) and Ambulatory PH Testing around The World in 2015. (17th August 2016) - Sweis, R; Fox, M
Abstract : Introduction: Despite advances in HRM and pH monitoring there is wide variation in technique and technology while reporting is often subjective and open to interpretation. This study assesses current practice around the world. Methods: Through an on-line platform (Qualtrics LLC), a survey was distributed to unselected oesophageal units through international NGM societies. Questions explored infrastructure, technology, analysis and reporting. Results are presented as % of the total or mean±SD. Results: 91 of 102 responses from 29 countries were analysable.(Table) 43 High (HVC) and 48 Low Volume Centres (LVC) were defined as more and less than 500 referrals/year. HVC employ more staff than LVC (p = 0.02) with more clinicians (3.0±1.0 vs. 2.6±1.2;p = 0.05), physiologists (1.6±1.1 vs. 2.0±1.3;p = 0.07) and nurses (3.3±1.2 vs. 2.4±1.1;p < 0.001). Most units (63/91;69%) stop medication. 18 (20%) use <12 sensor manometry, 75 (82%) >26 sensor HRM and 53 (58%) use HRM-Impedance (some had several systems). Adjunctive testing is increasingly incorporated.(Table) To define pathology, Chicago Classification is used in 65 (71%) units. 60% comment on the upper sphincter. In the presence of a hiatus hernia analysis of oesophago-gastric junction morphology varies widely (p=NS). 64% proceed with pH-monitoring despite ≥Grade B oesophagitis. If intolerant of the catheter, 45% refer for catheter-free monitoring and 16.5% for barium; 14% do nothing further. HVC are more likely to employ catheter-free systems than LVC (47% vs. 17%;p < 0.001). Of 86 (95%) units with Impedance-pH (Imp-pH), studies are performed on acid suppression in 54% with oesophagitis/Barrett's. Overall, 8% perform all Imp-pH studies on therapy, 9% never do. Dietary modification (acid avoidance) is always recommended in 48%. Meals/snacks are not analysed in 91% units with standard pH and 84% with Imp-pH. Overall 17% do not exclude meals with either. 75% manually analyse every Imp-reflux event while 59% only target symptoms. For symptom-association, 30% units pool symptoms while 74% analyse each separately. Therapy advice is included in 49% HVC and 31% LVC (p = 0.044); 40% overall. Conclusion: There is marked heterogeneity in methodology, interpretation and presentation of HRM and pH studies around the world. This survey sets the background from which agreement of standard operating procedures can begin. Disclosure of Interest: R. Sweis Conflict with: Symposium funded by Given Img, M. Fox: None Declared